Simulation optimisation of total cost in M/G/C retrial queuing systems with geometric loss, feedback and linear retrial policy. (6th March 2015) - Azadeh, Ali; Rizi, Seyedeh Salimian; Abdollahi, Mohammad; Fathi, Ehsan; Mahmoudi, Seyed Hamed
This paper presents an integrated computer simulation model for optimisation of total cost in an M/G/C retrial queue system with geometric loss, feedback and linear retrial policy. First, the computer simulation model is used to verify and validate an M/G/C retrial queue system. Second, certain important performance measures are obtained under steady–state condition. Finally, the simulation model is used to identify the preferred alternatives to optimise the current system. Significantly, it should be noted that there is no mathematical model to analyse an M/G/C retrial queue system. In this study, an integrated approach is used to develop the simulation model of the M/G/C retrial queue system. The objective of simulation model is to minimise the total cost and find the optimum solution. Also, a case study provided in which incoming calls of a clinic are modelled and analysed, because the most obvious retrial queue application lies in phone calls. This is the first study that utilises an integrated simulation approach for optimisation of total cost in an M/G/C queuing system with geometric loss and linear retrial policy.